2021
DOI: 10.1039/d1sc04153c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of symmetry-breaking of non-fullerene acceptors for efficient and stable organic solar cells

Abstract: The concurrent enhancement of the short-circuit current (JSC) and open-circuit voltage (VOC) is a key problem in the preparation of efficient organic solar cells (OSCs). In this paper, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
(52 reference statements)
0
28
0
Order By: Relevance
“…The results indicate that only one crystallization pattern is formed in the L8-BO:BTP-2F2Cl blend, confirming the formation of the alloylike phase. [32,34] Additionally, we have measured the PLQY of the corresponding acceptors (Figure S8, Supporting Information). The PLQY values of L8-BO, BTP-2F2Cl and L8-BO:BTP-2F2Cl are 3.2%, 5.5% and 3.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that only one crystallization pattern is formed in the L8-BO:BTP-2F2Cl blend, confirming the formation of the alloylike phase. [32,34] Additionally, we have measured the PLQY of the corresponding acceptors (Figure S8, Supporting Information). The PLQY values of L8-BO, BTP-2F2Cl and L8-BO:BTP-2F2Cl are 3.2%, 5.5% and 3.8%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Sun and co-workers developed an NFA named L8-BO by substituting the beta position of the thiophene unit on the Y6-central core with branched alkyl chains, [5] which exhibits upshifted energy levels and improved molecular packing, thus yielding a PCE of 18.32% with a FF of 81.5% in PM6:L8-BO OSCs. Apart from the terminal group and side-chain engineering, the asymmetric designs (in endgroups, [34,35] side-chains, [36] skeleton, [37][38][39] etc.) enable the photovoltaic systems to get further a step in device performance owing to the fine-tuning of photophysical and electrochemical properties, molecular orientation and stacking pattern, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that asymmetric structural modifications of NFAs were a valuable strategy for simultaneously promoting the photovoltaic performance and stability of OSCs. [69] In 2022, Chen et al developed an asymmetric FREA with the halogenated-thiophene-fused end group (CPTCN-Cl) and the halogenated-benzene-fused one (IC-2Cl), namely AC9, to fabricate the highly efficient OSCs. [82] The resulting PM6:AC9based binary OSC reached a record PCE of 18.43% (18.1% certified), with a V OC of 0.871 V, a J SC of 26.75 mA cm -2 , and an FF of 79.00%, higher than that (18.11%) of symmetrical classical acceptor BTP-eC9, [83] being ascribed to the sufficient charge transfer and reduced carrier recombination by a suitable concession between charge generation and non-radiative charge recombination.…”
Section: The Asymmetric End Groups-based Freasmentioning
confidence: 99%
“…Over the past few years, symmetric molecules containing two or more electron donor–acceptor (D–A) branches have been attracting considerable attention. These molecules are being increasingly used as two-photon absorbers, electron acceptors, or new luminescent materials in applications as diverse as fluorescence microscopy, , photopolymerization, , organic photovoltaics, , or organic light-emitting diodes. , Although these compounds do not possess a permanent electric dipole moment, their fluorescence usually exhibits a strong solvatochromism that is, in some cases, as large as that measured with the single-branched D–A analogue. This behavior was explained in terms of excited-state symmetry breaking (ES-SB), i.e., a transition from a symmetric and multipolar state to an asymmetric and dipolar state. , In principle, emission solvatochromism cannot be considered as an unambiguous evidence of ES-SB, unless it is as large as that of the single-branch analogue. Indeed, quadrupole–dipole and octupole–dipole interactions do also contribute to the solvation energy and, hence, give rise to a solvatochromism.…”
Section: Looking At Symmetry-forbidden Vibrational Transitionsmentioning
confidence: 99%
“…O ver the past few years, symmetric molecules containing two or more electron donor−acceptor (D−A) branches have been attracting considerable attention. These molecules are being increasingly used as two-photon absorbers, electron acceptors, or new luminescent materials in applications as diverse as fluorescence microscopy, 1,2 photopolymerization, 3,4 organic photovoltaics, 5,6 or organic light-emitting diodes. 7,8 Although these compounds do not possess a permanent electric dipole moment, their fluorescence usually exhibits a strong solvatochromism that is, in some cases, as large as that measured with the single-branched D−A analogue.…”
mentioning
confidence: 99%